Analisis Pengelolaan Arsip Digital Pada PT Anugrah Alam Karunia Abadi - Hayyina Farahdiba; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
The purpose of this research is to determine digital archive management which includes digital archive management facilities and to determine the positive impact of digital archive management for companies.This research uses a qualitative descriptive approach by describing and analyzing problems related to digital archive management. Primary and secondary data form the basis of qualitative research. Primary data for this research was obtained through documentation, observation, interviews and questionnaires, while secondary data was obtained from books, previous research and related articles.. From the results of this research, it can be seen that PT Anugrah Alam Karunia Abadi has not implemented digital archive management. However, the company is already discussing making a transition to digital archive management. In a comparison between the two methods, manual archives and digital archives, digital archive management increases the ease and speed of the sending, sharing and searching process. This also allows agencies to save physical storage space while providing more efficient access to users. Thus, this research shows that digital archive management can be beneficial for companies, such as improving operational efficiency and resource management. In the case of PT Anugrah Alam Karunia Abadi, implementing digital archive management can be a solution to increase the effectiveness of business processes and information management, and as a result, the company is expected to be able to take appropriate actions to implement digital archive management.